Explaining Vaccine Hesitancy: A Covid-19 Study of the United States - Rajeev K. Goel; James W. Saunoris (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using recent data on the unvaccinated across U.S. states, this paper focuses on the determinants of vaccine hesitancy related to the COVID-19 pandemic. Results show that more prosperous states and states with more elderly and physicians have lower vaccine hesitancy. There was some evidence of the significance of race, but internet access and history of other contagious diseases failed to make a difference. States with centralized health systems and those with mask mandates generally had a lower percentage of unvaccinated populations. Finally, the presence of Democrats in state legislatures tended to result in lower vaccination hesitancies, ceteris paribus.
Keywords: D11; I18; K42; 330; Covid-19; vaccination; vaccine hesitancy; pandemic; government; elderly; race religion; politics; United States